DEVELOPING BLENDED LEARNING APPLICATION UTILIZING ARTICULATE STORY LINE 3.0 INTEGRATED WITH ANDROID BASED SYSTEM - Efrizal Siregar; Nurianti Sitorus; Juwariah Juwariah (Jurnal Riset Informatika, 2021)
The development of science and technology in the digital era of Four Point Zero has a great impact on the world of education. One of them is by utilizing e-learning applications in the learning process. However, the technology used in this learning is too dependent on the internet network. Therefore, the research aims to develop a media in the form of an Android-based e-learning application that can be used online and offline. This study uses a research and development design using the ADDIE model. To create and test these products, in this case an Android-based e-learning application. Procedure This research was carried out through 6 stages, namely needs analysis, application design stage, development, data analysis, evaluation, and development of a final product that is ready to be used. From the results of the material validation test and the feasibility of the developed application media, it is very feasible to use.